1985
DOI: 10.1002/jcb.240290104
|View full text |Cite
|
Sign up to set email alerts
|

Molecular shape and self‐association of vinculin and metavinculin

Abstract: Vinculin, a 130,000-dalton protein localized to adhesion plaques, and metavinculin, a 150,-000 dalton protein closely related to vinculin, have been studied using rotary shadowing and electron microscopy. Both proteins have globular head regions attached to rod-shaped tail domains. Vinculin and metavinculin also both form complexes consisting of four to six individual molecules. These multimers are formed by head-to-head as well as tail-to-tail interactions. Talin, another protein which has been localized to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(56 citation statements)
references
References 14 publications
4
52
0
Order By: Relevance
“…They suggested that vinculin might selfassociate in focal contacts. Evidence for self-association of vinculin molecules has now been obtained from both direct binding assays (Otto, 1983;Belkin and Koteliansky, 1987) and EM (Milam, 1985;Molony and Burridge, 1985). We propose that self-association of vinculin molecules is responsible for the nonproportional inhibition of talin binding by unlabeled vinculin in our own experiments.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…They suggested that vinculin might selfassociate in focal contacts. Evidence for self-association of vinculin molecules has now been obtained from both direct binding assays (Otto, 1983;Belkin and Koteliansky, 1987) and EM (Milam, 1985;Molony and Burridge, 1985). We propose that self-association of vinculin molecules is responsible for the nonproportional inhibition of talin binding by unlabeled vinculin in our own experiments.…”
Section: Discussionsupporting
confidence: 58%
“…Thus, when a partial eDNA encoding just the COOH-terminal tail of vinculin is expressed in Cos cells, the polypeptide localizes to adhesion plaques, as does the vineulin encoded by cVin5 (Bendori et al, 1989). The tail region of vinculin is known to be a selfassociation site (Molony and Burridge, 1985;Milam, 1985), and it therefore seems likely that the expressed tail polypeptides are simply associating with endogenous monkey vineulin. The COOH-terminal tail region of vinculin is predicted to be basic relative to the globular head, which is predicted to be acidic (Coutu and Craig, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…As shown in supplemental Fig. S3C, multiple higher order Vt species form in the absence of actin and the ability for vinculin to form these higher order oligomers has been previously observed (46,47). Because these higher order Vt oligomers disappear with increasing actin concentrations and because Vt ⌬C5 is a F-actin bundling-deficient mutant, we have chosen to focus on changes in the dimer and trimer bands between WT Vt and Vt ⌬C5 with increasing concentrations of actin.…”
Section: Vt Association With F-actin Promotes Vt Dimerization-vtsupporting
confidence: 65%
“…This study demonstrates, however, that vinculin binds to E-cadherin complexes in the absence of ␣-catenin, which eliminates binding to ␣-catenin as the sole mechanism for the targeting of vinculin to the adhesion complex. The possibility that vinculin may cross-link adhesion complexes is inferred from electron microscopy studies of rotary-shadowed vinculin that demonstrate the existence in vitro of vinculin complexes containing two to six individual molecules (45,46). It remains to be determined whether this multimerization takes place in vivo.…”
Section: Discussionmentioning
confidence: 99%